Effect of alternative fungicides and inoculation strategy on yeast biodiversity and dynamics from the vineyard to the winery. (December 2022) - Englezos, Vasileios; Mota-Gutierrez, Jatziri; Giacosa, Simone; Río Segade, Susana; Pollon, Matteo; Gambino, Giorgio; Rolle, Luca; Ferrocino, Ilario; Rantsiou, Kalliopi
Graphical abstract: Highlights: Effect of antifungal compounds against powdery and downy mildew at the vineyard. Treatment-dependent effect on the load and diversity of yeast populations on grapes. Winery fermentations further influenced yeast ecology in fermentations. Fermentation kinetics were correlated to the treatment used. Wine characteristics are influenced by harvesting and post-harvesting interventions. Abstract: Fungi and oomycetes found in vineyards cause diseases such as powdery and downy mildew. Consequently, conventional and alternative agronomical practices are widely used prior to harvest to protect grapes. Alternative products are considered more eco-friendly and environmentally sustainable in comparison to conventional chemical products. However, the effect of these alternative products on yeast ecology, from the vineyard to the winery, is poorly understood. This study compared the effect of alternative and conventional chemical antifungal compounds (copper and sulphur based) on grapes' mycobiota in the vineyard and during subsequent winery fermentation using culture-dependent and -independent approaches. Culture-dependent data indicated a treatment-dependent effect on the load and diversity of yeast populations on grapes. It was found that the population of Hanseniaspora uvarum was higher on grapes previously treated with laminarin and copper, compared to the other levels registered on grapes previously treated with the rest of antifungal products tested in this study (including the untreated and conventional treatment controls). Concerning, wine quality, the chemical composition was not correlated to the application of antifungal treatment in the vineyard. Understanding the effect of different antifungal products on grape and wine microbial communities may help in setting up guidelines for wine grape production. These guidelines, can be used to guarantee quality in the pursuit of a sustainable competitive advantage in the market.